PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER UNTUK MENINGKATKAN AKTIVITAS SISWA KELAS VII-A SMPNEGERI 1PANYABUNGAN UTARA - Nurhamidah Nurhamidah (Universitas Negeri Medan, 2017)
Abstract: Application of Advance Organizer Learning Model to Increase Student Activity in Class VII-A SMPN 1 Panyabungan Utara. This classroom action research will be done in two cycles. From cycle to cycle using Advance Organizer learning model by constantly improving the quality of learning activityoriented student activity that will lead to improvement of student learning outcomes. The research is applied to the students of class VII-A SMP Negeri 1 Panyabungan Utara, with the number of 23 students. The results showed that the data of student activity according to the two observer observations in Cycle I were: writing / reading (38,3%), doing (25%), asking fellow friend (19,2%), asking teacher (10.8% ), and which are not relevant to KBM (6.7%). And the data of student activity according to the observation in Cycle II are: writing / reading (31,8%), work (40,9%), ask fellow friend (17,3%), ask teacher (7,3%), and which is not relevant to KBM (2.7%). Keywords: Advance Organizer Learning Model, Student Activity Improvement Abstrak : Penerapan Model Pembelajaran Advance Organizer Untuk Meningkatkan Aktivitas Siswa Di Kelas VII-A SMPN 1 Panyabungan Utara.Penelitian tindakan kelas ini akan ditempuh dalam dua siklus. Dari siklus ke siklus menggunakan model pembelajaran Advance Organizer dengan senantiasa meningkatkan kualitas pelaksanaan pembelajaran yang berorientasi aktivitas siswa yang akan bermuara pada perbaikan hasil belajar siswa. Penelitian dikenakan pada siswa kelas VII-A SMP Negeri 1 Panyabungan Utara, dengan jumlah 23 siswa. Hasil penelitian menunjukkan Data aktivitas siswa menurut kedua pengamatan pengamat pada Siklus I antara lain: menulis/membaca (38,3%), mengerjakan (25% ), bertanya sesama teman (19,2%), bertanya kepada guru (10,8%), dan yang tidak relevan dengan KBM (6,7%). Dan Data aktivitas siswa menurut pengamatan pada Siklus II antara lain: menulis/membaca (31,8%), bekerja (40,9%), bertanya sesama teman (17,3%), bertanya kepada guru (7,3%), dan yang tidak relevan dengan KBM (2,7%). Kata Kunci:Model Pembelajaran Advance Organizer, Peningkatan Aktivitas Siswa